Laura Méndez de Cuenca : Mexican Feminist, 1853-1928 - Bazant de Saldaña, Mílada (The University of Arizona Press, 2018)
The exciting and heartbreaking biography of a woman willing to fight for liberation during a tumultuous time in Mexican history--Provided by publisher.